2023
DOI: 10.1101/2023.12.20.572718
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Concerted SUMO-targeted ubiquitin ligase activities of TOPORS and RNF4 are essential for stress management and cell proliferation

Julio C.Y. Liu,
Leena Ackermann,
Saskia Hoffmann
et al.

Abstract: SummaryProtein SUMOylation provides a principal driving force for cellular stress responses including DNA-protein crosslink (DPC) repair and arsenic-induced PML body degradation. In genome-scale screens, we identified the human E3 ligase TOPORS as a key effector of SUMO-dependent DPC resolution. We demonstrate that TOPORS promotes DPC repair by functioning as a SUMO-targeted ubiquitin ligase (STUbL) for DPCs, combining ubiquitin ligase activity through its RING domain with poly-SUMO chain binding via a cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Parallel investigations by others performing similar CRISPR screens identified TOPORS as a SUMO-targeted ubiquitin E3 ligase that acts in semi-redundant concert with RNF4 to mediate efficient proteasomal degradation of DNA-adducted DNMT1 62,63 . Nonetheless, our 20 data strongly indicate that ubiquitylation of SUMOylated DNMT1 adducts is not the only mechanism by which TOPORS protects HMA-exposed cells from DDR-induced apoptosis.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Parallel investigations by others performing similar CRISPR screens identified TOPORS as a SUMO-targeted ubiquitin E3 ligase that acts in semi-redundant concert with RNF4 to mediate efficient proteasomal degradation of DNA-adducted DNMT1 62,63 . Nonetheless, our 20 data strongly indicate that ubiquitylation of SUMOylated DNMT1 adducts is not the only mechanism by which TOPORS protects HMA-exposed cells from DDR-induced apoptosis.…”
Section: Discussionmentioning
confidence: 89%
“…Parallel investigations by others performing similar CRISPR screens identified TOPORS as a SUMO-targeted ubiquitin E3 ligase that acts in semi-redundant concert with RNF4 to mediate efficient proteasomal degradation of DNA-adducted DNMT1 62,63 Our proteomics identified RNA splicing factors as key candidates for TOPORS-mediated SUMOylation or ubiquitylation in AML cells, even in the absence of HMA, and characterized widespread mis-splicing of DNA repair genes in TOPORS-edited cells, likely due in part to aberrant SUMO-or ubiquitin-modulation of interacting splicing factors. These results draw similarities to a recent study which showed that splicing modulators targeting SF3B1 triggered enhanced exon-skipping in DNA damage repair genes 64 .…”
Section: Discussionmentioning
confidence: 90%
“…DPC proteolysis can be initiated upon collision with the DNA replication machinery 18 causing SPRTN activation 13,19 and replication-coupled ubiquitylation, targeting DPCs for proteasomal degradation 13,20 . Additionally 3,[10][11][12] , global-genome (GG) DPC repair occurs through DPC SUMOylation and subsequent SUMO-dependent polyubiquitylation by RNF4 or TOPORS, which triggers proteasomal degradation [21][22][23][24][25] or cleavage by SPRTN 26 .…”
Section: Csb Promotes Recovery From Dpc-induced Transcription Arrestmentioning
confidence: 99%